Pioneer Sisters: Little House # 2 : adapted from The Little house books by Laura Ingalls Wilder - Wilder, Laura Ingalls, 1867-1957; Peterson, Melissa (Melissa A.); Kim, Ji-Hyuk (New York, NY : Harper, an imprint of HarperCollinsPublishers, 2017)
Laura, Mary, and Carrie play games, find mischief, and explore the wild as they travel and settle throughout the Midwest.
Keywords: Wilder, Laura Ingalls, -- 1867-1957 -- Fiction; Family life -- Fiction; Frontier and pioneer life -- Fiction; Sisters -- Fiction